Determinación de Valores Séricos y Factores asociados en Caninos Domésticos (canis familiaris) en el Barrio San Bartolome de la Parroquia San Juan de Pastocalle. - Ortiz Sevilla, Kevin Patricio (2018)
Due to the fact that the domestic canines presented several diseases of zoonotic nature, it was necessary to implement the present research having as main objective to determine the serum values and associated factors at domestic dogs (Canis familiaris), through the analysis of blood samples allowing it to prove the conditions that suffer from the canines of the neighborhood of San Bartolomé. At this investigation, a survey was conducted to the owners of 75 canines that were part of this job, where associated factors and the mode of possession presented by the canines were determined, as well as a clinical record of each one of the them under study. The process of collecting blood samples was performed using the cephalic vein venipuncture technique, and it was collected in red cap vacutainer tubes 3ml and vacutainer cap lilac 2ml, the groups are included, in two age groups regardless of race or gender, 61 canines within the range of 1 to 5 years and 14 canines are in the range of 5 years and up. The referential results obtained at this study were similar to the data published in other studies, however it was found cases in which they differ from the literature, so it is taken into account that the canines experienced at this investigative work reside at a height of 3.197msnm, thus obtaining the following results; of red blood cells, elevated hematocrit was 30.68 and decreased was 1.64, the white blood cells, the elevated leukocytes was 17.56 and decreased was 9.84, the blood chemistry decreased, the glucose was 14.25 and increased was 47.48, Urea the increased value was 19.20 and decreased was 6.56, the high BUN values was 3.28 and decreased was 13.19, in the elevated Creatinine was 15, 34 and decreased was 1.64, the high AST was 7.14 while there were no low levels and the high ALT was 2.48.